ASSOCIATION BETWEEN EXCLUSIVE BREASTFEEDING PRACTICE, TABURIA SUPPLEMENTATION, AND STUNTING PREVALENCE AMONG CHILDREN AGED 24–60 MONTHS IN SIDOTOPO WETAN, SURABAYA - Firda Sahdani; Emyr Reisha Isaura; Sri Sumarmi (Media Gizi Indonesia, 2021)
Stunting is a condition in which a child’s height is shorter than other children of the same age. Exclusive breastfeeding is a factor that can aff ect the stunting prevalence in Indonesia. In addition, specifi c nutritional intervention through multi-micronutrient supplementation called Taburia is given to prevent stunting. This study was aimed to determine the relationship between exclusive breastfeeding practice and taburia supplementation in children aged 24-60 months in the working area of Sidotopo Wetan Health Center, Surabaya City. This study used secondary data obtained from a child monitoring survey database from the Surabaya City Health Offi ce in the working area of Sidotopo Wetan Health Center. The samples size was 141 children aged 24–60 month, and the statistical analysis employed was the chi-square test. The results showed that the stunting proportion was 54.60%. There was a relationship between exclusive breastfeeding practice and the stunting incidence (p = 0.047). Children who did not provide exclusive breastfeeding had a higher risk 1.97 times of stunting. Taburia supplementation also had a signifi cant relationship with stunting incidence (p = 0.016). Children with non taburia had a higher risk 2.35 times of stunting. Based on these results, it can be concluded that the prevention of stunting can be overcome by maximizing exclusive breastfeeding practice and complementary foods, also the allocation of taburia